Genomic analysis of Plasmodium vivax field isolates circulating in sub-Saharan Africa - Isabelle Bouyssou; Lemu Golassa; Inès Vigan-Womas; Matthieu Schoenhals; Arsène Ratsimbasoa; Ali Ould Mohamed Salem Boukhary; Maria de Fátima Ferreira-da-Cruz; Sandrine Houzé; Laurence Ma; Feng Lu; Chetan Chitnis; Pascal Campagne; et al. (Communications Biology)
Abstract Plasmodium vivax malaria is a major public health problem outside sub-Saharan Africa. However, an increasing number of P. vivax infections in Duffy-negative individuals has been reported across Africa in recent years, raising concerns that the parasites may have evolved alternative pathways to invade reticulocyte and overcome Duffy-negativity. Here, we investigated the global genetic structure and diversity of sub-Saharan African P. vivax populations, exploring possible molecular signatures of adaptation to Duffy-negative hosts. We analyzed 204 previously published P. vivax genome sequences from Africa, Southeast Asia, the Pacific Coral Triangle, and South America and generated whole-genome sequences of 133 P. vivax field isolates collected from 10 sub-Saharan African countries. Our analysis revealed four distinct geographic clusters, with clear contrasts between East/West Africa and the Indian Ocean populations. Despite the limited number of interpretable sequences from Duffy-negative individuals - attributable to low parasitemia - and the lack of clear evidence of selective pressure acting on invasion-related genes of the P. vivax parasite populations circulating in sub-Saharan Africa, our study offers valuable insights into the genetic diversity of P. vivax and lays the groundwork for future research exploring parasite adaptation to Duffy-negative hosts.